(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The humanist approach to legal theory displays many of the features of legal naturalism, in that this intellectual movement sees justice as inspiring legal practise andas underlying positive laws. Other schools of thought in the philosophy of law, suchas legal positivism and legal realism, by failing to provide an essential integration of justice and its contents, are less closely aligned to legal humanism. This approachrequires some examination of Stoic thought which, in writers like Chrysippus and Cicero, shapes a universalist view of Natural Law. Sixteenth- and seventeenth-century Spanish legal philosophers such as Vázquez de Menchaca, Francisco Suárez,Luis de Molina and Gabriel Vázquez were outstanding legal humanists. Their work tends to secularise the foundations of Law, highlighting the just and objective nature of the interhuman actions required for coexistence, and provides modern support for the idea of subjective natural rights.